2001
DOI: 10.2307/3558402
|View full text |Cite
|
Sign up to set email alerts
|

Allozyme diversity in three endemic species ofCistus(Cistaceae) from the Canary Islands: intraspecific and interspecific comparisons and implications for genetic conservation

Abstract: IMPLICATIONS MlIC GENETIC CONSERVATTON~1ManuxnprCmMd6Jlme200Q,rrvigmacocptcd ISFcbnrarya001.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 65 publications
2
29
0
Order By: Relevance
“…Thus, although Eguiarte et al (1992) found a similar value to P. canariensis' in the rain forest palm Astrocaryum mexicanum (He ¼ 0.153), lower values were described in Carpentaria acuminata, (He ¼ 0.143), Ptychosperma bleeseri (He ¼ 0.006) and Pinanga tenella (He ¼ 0.133) (Shapcott, 1998a(Shapcott, , b, 1999 and in Washingtonia filifera (He ¼ 0.008) (McClenaghand and Beauchamp, 1986). This result agrees with other studies that show higher genetic diversity levels in Canarian endemic plants than in those distributed in other oceanic islands (Francisco-Ortega et al, 2000;Batista et al, 2001;Batista and Sosa, 2002;Bouza et al, 2002). On the whole, the three groups of populations exhibited higher genetic variability values than species with similar life history traits (monocotyledons, endemics and species with sexual reproduction).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Thus, although Eguiarte et al (1992) found a similar value to P. canariensis' in the rain forest palm Astrocaryum mexicanum (He ¼ 0.153), lower values were described in Carpentaria acuminata, (He ¼ 0.143), Ptychosperma bleeseri (He ¼ 0.006) and Pinanga tenella (He ¼ 0.133) (Shapcott, 1998a(Shapcott, , b, 1999 and in Washingtonia filifera (He ¼ 0.008) (McClenaghand and Beauchamp, 1986). This result agrees with other studies that show higher genetic diversity levels in Canarian endemic plants than in those distributed in other oceanic islands (Francisco-Ortega et al, 2000;Batista et al, 2001;Batista and Sosa, 2002;Bouza et al, 2002). On the whole, the three groups of populations exhibited higher genetic variability values than species with similar life history traits (monocotyledons, endemics and species with sexual reproduction).…”
Section: Discussionsupporting
confidence: 81%
“…Of the 43 alleles, 39 were common to both Phoenix species analysed, and this furnishes evidence of their shared evolutionary history. In a recent survey, the sharing of 14 of the 25 total alleles detected in five Canarian taxa of Cistus (Batista et al, 2001) was used to support the close phylogenetic relationship among them. Similarly, a close relatedness between two Brighamia species from Hawaii was inferred from their sharing of only six alleles out of 22 (Gemmill et al, 1998).…”
Section: Genetic Relationships Within Among Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, an accurate estimate of the level and distribution of genetic diversity of threatened and endangered species is an important element in designing conservation programs (Hamrick et al 1991;Schaal et al 1991;Chalmers et al 1992;Cardoso et al 1998). Studies on genetic diversity within and among populations of insular endemic plant species using molecular markers have increased in recent years due to their central importance in planning in situ and ex situ conservation efforts (e.g., de Joode and Wendel 1992; Gemmill et al 1998;FranciscoOrtega et al 2000;Crawford et al 2001;Batista et al 2001;Bouza et al 2002). Three reviews compiled from both the Pacific and Atlantic Oceans (de Joode and Wendel 1992;Francisco-Ortega et al 2000;Crawford et al 2001) showed low diversity in insular endemics in general and suggested that there is lower variation within species of Pacific Island endemics than in the Canary Island endemics.…”
Section: Introductionmentioning
confidence: 98%
“…No reliable guidelines have been developed for determining the number of transplant individuals required, but the optimal number would increase with diversity in donor populations (e.g., Pavlik 1996, Vogler 1998, Batista et al 2001. Analysis of DNA could demonstrate levels of variation in regions of the genome, but this is not generally done for transplant experiments (Gordon and Rice 1998).…”
Section: Transplant Techniquesmentioning
confidence: 99%